Gender differences in risk factors for suicide attempts among young, first-episode and drug-naive major depressive disorder patients with anxiety symptoms - Jiang, Donghong; Lang, XiaoE; Wang, Dongmei; Zhang, Xiang-Yang (Frontiers in Psychiatry, 2024)
Background: Suicide attempts and anxiety are common commodities in patients with major depressive disorder (MDD), and suicide attempts are often associated with anxiety symptoms.Studies have found gender differences in several aspects of MDD; however, gender differences in suicide attempts in young first-episode and drug-naive (FEDN) MDD patients with anxiety remain unknown. This study aimed to investigate potential gender differences in the prevalence of suicide attempts and associated risk factors among young FEDN MDD patients with anxiety in a Chinese Han population.A cross-sectional study was conducted on 1289 young patients with FEDN MDD. Demographics, clinical characteristics, and biochemical parameters of patients were collected.Results: Suicide attempters accounted for 23.80% and 26.12% of male and female FEDN MDD patients with anxiety, respectively, with no significant gender differences. Binary logistic regression analyses showed that anxiety, clinical global impression severity, and thyroid peroxidase antibody significantly predicted suicide attempts in both male and female FEDN MDD patients with anxiety, while body mass index significantly predicted suicide attempts only in males, and psychotic symptoms predicted suicide attempts only in females.The present study represents the first large-scale investigation of gender differences in the prevalence of suicide attempts and related risk factors among young FEND MDD patients with anxiety in the Chinese Han population. The results indicate that risk factors associated with suicide attempts vary by gender among young FEND MDD patients with anxiety, although a comparable rate of suicide attempts was observed in both female and male patients.